Framboids - Rickard, David T. 1943- (Oxford University Press, 2021)
"Framboids may be the most astonishing and abundant natural features you have never heard of. These microscopic spherules of golden pyrite consist of thousands of even smaller microcrystals often arranged in stunning geometric arrays. There are probably 1030 on Earth and they are forming at a rate of 1020 every second. This means that there are a billion times more framboids than sand grains on Earth and a million times more framboids than stars in the observable universe. They are all around us: they can be found in rocks of all ages and in present-day sediments, soils and natural waters. The sulfur in the pyrite is mainly produced by bacteria and many framboids contain organic matter. They are formed through burst nucleation of supersaturated solutions of iron and sulfide followed by limited crystal growth in diffusion-dominated stagnant sediments. The framboids self-assemble as surface free energy is minimized and the microcrystals are attracted to each other by surface forces. Self-organization occurs through entropy maximization and the microcrystals rotate into their final positions through Brownian motion. The final shape of the framboids is often actually polygonal or partially facetted rather than spherical, as icosahedral microcrystal packing develops. Their average diameter is around 6 microns and the average microcrystal size is about 0.1 microns. There is no significant change in these dimensions with time: the framboid is an exceptionally stable structure and the oldest may be 2.9 billion years old. This means that they provide samples of the chemistry of ancient environments"--